Factors related to the level of iron adequacy of adolescent girls in Indonesia - Febiani Riskika; Dodik Briawan; Ikeu Tanziha (AcTion: Aceh Nutrition Journal, 2023)
Anemia remains a nutritional problem in Indonesia, where more than 50% of the incidence is due to iron deficiency caused by low quality and quantity of food consumed and iron intake sources. Low iron intake did not affect iron adequacy. This study aimed to analyze the factors associated with iron adequacy among adolescent girls in Indonesia. This study used a cross-sectional design and secondary data from the National Survey of Food Consumption (NSFC) in Indonesia in 2014. The number of participants was 11.766 adolescent girls aged 10-18 years. Data were collected using the NSFC 2014 questionnaire and the food consumption collection method using a food recall 24 hour. Statistical analysis was performed using the chi-squared test and Logistic Regression to identify the factors influencing iron adequacy. The results showed that the iron intake of adolescent girls in Indonesia was 10 mg/day, with an adequate iron level of 42,9%. Logistic regression showed that the most influential factors (p<0,05) were age, place of residence, economic status, and consumption of cereals, vegetables, nuts, fruits, and animal foods. In conclusion, the factors associated with the iron adequacy level of adolescent girls in Indonesia are age, region of residence, economic status, and consumption of cereals, vegetables, nuts, fruits, and animal foods.